2017
DOI: 10.1017/s0266078417000396
|View full text |Cite
|
Sign up to set email alerts
|

The discursive construction of English naming practice in Mainland China: A nationalism and authenticity perspective

Abstract: Recently, a regional newspaper agency in Mainland China reported on the Chinese celebrity Angelababy by using her English name (Net Ease Entertainment, 2016). A reader complained about this, suggesting that Angelababy's Chinese name needs to be in the report as well. The reader's comment and the name Angelababy went viral on many online news outlets, and comments were posted about the problems associated with such an English name from a large number of Chinese netizens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Regarding English language instruction, research has also shown that language teachers are very influential in Chinese students' decisions to adopt non-Chinese names (Chen 2015;Chen 2021;Edwards 2006). In selecting and embracing their new names, Chinese students have also been found to modify their identities to accommodate to the foreign language classroom (Cotterill 2020;Wang & Yao 2018). At the same time, Chinese students often attempt to find an English name that suits their personality (Cotterill 2020;Henry 2012).…”
Section: Adopting Foreign Names By Chinese Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding English language instruction, research has also shown that language teachers are very influential in Chinese students' decisions to adopt non-Chinese names (Chen 2015;Chen 2021;Edwards 2006). In selecting and embracing their new names, Chinese students have also been found to modify their identities to accommodate to the foreign language classroom (Cotterill 2020;Wang & Yao 2018). At the same time, Chinese students often attempt to find an English name that suits their personality (Cotterill 2020;Henry 2012).…”
Section: Adopting Foreign Names By Chinese Studentsmentioning
confidence: 99%
“…As a result, Western personal names are becoming increasingly used by certain Chinese professionals who are work in foreign-investment corporations or Western educational circles. Although English and French are both official languages used in the United Nations and serve as popular international languages, the number of Chinese people who have English names still surpasses the number of Chinese people who have a French name as their foreign identification marker (Cheang 2008;Wang & Yao 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Xu's (2018) experience emphasized the 'identity dilemma' of Chinese English learners (Ye, 2017, p. 17). Although English has been positioned as central to educational and economic success, many Chinese critics of global English have recognized that language learning and the adoption of English names may threaten nationalism and cultural homogenization (Wang & Yao, 2018). In this sense, the adoption of English names should not be seen exclusively as a disinterested linguistic endeavour; threads of globalization and cosmopolitanism are woven throughout the various reasons Chinese individuals give for adopting Anglo-Saxon names (Diao, 2014).…”
Section: Chinese Learners and The Adoption Of English Namesmentioning
confidence: 99%
“…The term "discursive construction" is used for different purposes depending on the subject of the study. So, we can talk about discursive construction of social world (Makarov, 2003;Filinskij, 2002); national identities (Wodak, et al, 2009); teacher identities (Delarue & Lybaert, 2016); identities in a social network-educational space (Chau & Lee, 2017); language attitudes among the Japanese youths (Saito, 2014); knowledge and equity in classroom interactions (Shepherd, 2014); intercultural relations (Liddicoat, 2013); experience of intercultural communication in a biographical narrative (Smirnova, 2011); empathy, goodwill, "democracy in action", solidarity (Plotnikova, 2011;Plotnikova, 2015); historical memory (Drugovejko, 2014); a world-class city (Flowerdew, 2004); scientific (un)certainty about the health risks of China's air pollution (Liu & Zhang, 2018); contested environmental issues in the news media (Lidskog & Olausson, 2013); English naming practice in Mainland China in the perspective of nationalism and authenticity (Wang & Yao, 2018), etc.…”
Section: Introduction and Theoretical Frameworkmentioning
confidence: 99%